Literature Review Company Policy: Workload, Work Time and Employee Compensation - Hermawan, Eric (Journal of Law, Politic and Humanities, 2021)
This study discusses the workload given by the company or organization to its employees, working hours, and compensation provided to employees. However, the company's policies regarding workload, working hours, and compensation violate existing rules. In this study, researchers used descriptive qualitative methods and library research by conducting an analysis based on articles relevant to the variables above. Then collect data from Google Scholar related to previous research articles and use Mendeley as a reference. The study results are 1) Workload related to company policy, 2) working time related to company policy, and 3) employee compensation related to company policy.